2019
DOI: 10.1111/hepr.13443
|View full text |Cite
|
Sign up to set email alerts
|

CD133 and epithelial cell adhesion molecule expressions in the cholangiocarcinoma component are prognostic factors for combined hepatocellular cholangiocarcinoma

Abstract: Aim A new classification of combined hepatocellular cholangiocarcinoma (CHC) was recently reported. Cancer stem cells have been associated with CHC carcinogenesis. This study examined the association of cancer stem cell marker expression and prognosis in CHC classified using the new classification. Methods We enrolled 26 CHC patients and classified them according to the new classification. We evaluated the expression of cancer stem cell markers (CD56, CD133, and epithelial cell adhesion molecule [EpCAM]) by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…By comparing the gene expression profiling between the two subtypes, we found that the aggressive Cluster2 tumors had significantly upregulated expression of stemness-related genes such as CA9, EpCAM, MMP9, KRT19, CD24, and PROM1 (CD133). These are well-known markers of stemness traits and are associated with poorer prognostic outcomes in HCC [18,[59][60][61][62]. Based on integrative analysis of genomic and epigenomic data in liver cancer, Woo et al also identified one aggressive cluster of the HCC subtype (iCl1) with the previously mentioned stemness-related genes being on top of the upregulated genes [17], which is similar to our finding.…”
Section: Discussionsupporting
confidence: 90%
“…By comparing the gene expression profiling between the two subtypes, we found that the aggressive Cluster2 tumors had significantly upregulated expression of stemness-related genes such as CA9, EpCAM, MMP9, KRT19, CD24, and PROM1 (CD133). These are well-known markers of stemness traits and are associated with poorer prognostic outcomes in HCC [18,[59][60][61][62]. Based on integrative analysis of genomic and epigenomic data in liver cancer, Woo et al also identified one aggressive cluster of the HCC subtype (iCl1) with the previously mentioned stemness-related genes being on top of the upregulated genes [17], which is similar to our finding.…”
Section: Discussionsupporting
confidence: 90%
“…S1A-B). Numerous studies suggest that CD133, CD24, CD44, EpCAM, Sox2, and CD49f are biomarkers for the identification of cancer stem-like cells (CSCs) in cholangiocarcinoma [31] , [32] , [33] , [34] , [35] , [36] . To examine the CSC marker expression levels in CSCs after altering ALKBH5 expression, RT-qPCR was conducted to detect RNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Although microsatellite instability relatively frequently occurred in in intraductal papillary neoplasms of the biliary tract, the methylation of hMLH1 was not detected [49] . EpCAM, a stemness-related marker, is positively with the aggressive prognosis in ICC and HCC [50][51] . However, we didn't observe an association between INTS8 and EpCAM in ICC.…”
Section: Discussionmentioning
confidence: 99%